2010
DOI: 10.3168/jds.2010-3201
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body condition score at calving and supplementation with Saccharomyces cerevisiae on milk production, metabolic status, and rumen fermentation of dairy cows in early lactation

Abstract: The objective of this study was to examine the effects of live yeast (LY) supplementation and body condition score (BCS, 1-5 scale) at calving on milk production, metabolic status, and rumen physiology of postpartum (PP) dairy cows. Forty Holstein-Friesian dairy cows were randomly allocated to a 2 × 2 factorial design and blocked by yield, parity, BCS, and predicted calving date. Treatments were body condition at calving (low for BCS ≤3.5 or high for BCS ≥3.75; n=20) and supplementation with LY (2.5 and 10 g o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 68 publications
11
33
1
Order By: Relevance
“…The same results was found by Al Ibrahim et al [2] comparing yeast supplementation of dairy cows with high or low BCS (BCS ≤ 3.5 and BCS ≥ 3.75) assuming that yeast supplementation has no effect in DMI and thus in the BCS. According to Petrera et al [25] there is a negative correlation between BCS and NEFA in the early postpartum period and this information explains the results observed in the present study where BCS declines in the SG are followed by a NEFA increase.…”
Section: Discussionsupporting
confidence: 76%
“…The same results was found by Al Ibrahim et al [2] comparing yeast supplementation of dairy cows with high or low BCS (BCS ≤ 3.5 and BCS ≥ 3.75) assuming that yeast supplementation has no effect in DMI and thus in the BCS. According to Petrera et al [25] there is a negative correlation between BCS and NEFA in the early postpartum period and this information explains the results observed in the present study where BCS declines in the SG are followed by a NEFA increase.…”
Section: Discussionsupporting
confidence: 76%
“…The response of rumen fermentation profile to yeast supplements lacks consistency. Pinloche et al (2013) reported increased proportions of propionate and butyrate in rumen fluid in response to yeast, increased proportions of propionate (Erasmus et al, 2005), acetate (Al Ibrahim et al, 2010), and butyrate (Thrune et al, 2009) have been reported, as well the absence of the effect of yeast on rumen fermentation profile (Bitencourt et al, 2011;Ferraretto et al, 2012). Yeast-supplemented cows had higher PUN than control, also observed by Zaworski et al (2014) in postpartum cows, suggesting increased proteolytic activity in the rumen (Yoon and Stern, 1996).…”
mentioning
confidence: 69%
“…Accumulating intrahepatic acetyl CoA levels are encountered by the formation and export of ketone bodies (incomplete oxidation). Thus, cows with a high extent of fat mobilization have not only greater plasma NEFA (1.3-2-fold) but generally also greater BHBA (1.8-3-fold) concentrations and greater a liver lipid content as compared with cows with lesser fat mobilization [54,55,67]. Excessive circulating BHBA concentrations concomitant with a hepatic lipid content greater than 10% wet weight may have negative effects on metabolic health and productivity [16,66].…”
Section: Livermentioning
confidence: 92%